Monitoring of miR-181a-5p and miR-155-5p Plasmatic Expression as Prognostic Biomarkers for Acute and Subclinical Rejection in de novo Adult Liver Transplant Recipients - Millán, Olga; Ruiz, Pablo; Orts, Lara; Ferré, Paula; Crespo, Gonzalo; Santana, Miguel; Fortuna, Virginia; Quintairos, Luís; Navasa, Miguel; Brunet, Mercè (Frontiers in Immunology, 2019)
Background & Aims: News strategies for the accurate assessment of the state of immunosuppression (IS) in liver transplant recipients are needed to prevent rejection and minimize drug-related side effects. miRNAs can potentially be used as diagnostic or prognostic biomarkers in transplant patients. This study evaluated the capacity of a plasmatic miRNA panel (miR-155-5p, miR-122-5p, miR-181a-5p and miR148-3p) as an early non-invasive prognostic and diagnostic biomarker for T cell-mediated acute rejection (TCMAR) and subclinical rejection (SCR) in adult liver recipients. Methods: A total of 145 liver recipients were included. All patients received a calcineurin inhibitor with or without mycophenolate mofetil and methylprednisolone. Plasmatic miRNA expression was assessed by qPCR before and at different time-points after liver transplantation. Results: Seventeen patients experienced TCMAR, and eight were diagnosed with SCR during the protocol biopsy at the 3rd month post-transplantation. Pre-transplantation, miR-155-5p expression was significantly higher in TCMAR patients and in SCR patients than in non-rejectors, and miR-181a-5p expression was also significantly higher in SCR patients than in non-rejectors. Post-transplantation, before transaminase-level modification, significantly increased miR-181a-5p, miR-155-5p, and miR-122-5p expression was observed in TCMAR and SCR patients. Binary logistic regression analyses showed, post-transplantation, that TCMAR risk was better predicted by individual expression of miR-181a-5p (LOGIT=-6.35+3.87*miR-181a-5p), and SCR risk was better predicted by the combination of miR-181a-5p and miR-155-5p expression (LOGIT=-5.18+2.27*miR-181a-5p+1.74*miR-155-5p). Conclusions: Pre-transplantation plasmatic miR-155-5p expression may be useful for stratifying low-immunologic-risk patients, and post-transplantation miR-181a-5p and miR-155-5p may be candidates for inclusion in early, non-invasive prognostic biomarker panels to prevent TCMAR or SCR and better identify patient candidates for IS minimization. Large prospective randomized multicenter trials are needed to refine the cut-off values and algorithms and validate the clinical usefulness of these biomarkers.